House Doctor : A-Z of Design - Maurice, Ann and Blake, Fanny (London HarperCollins Publishers, 2000)
The focus of this book is not on dramatic or extreme makeovers, but on styling the home you have to maximum advantage. While aimed primarily at people wishing to sell their home, the book also provides plenty of ideas for people looking to smarten up their property, both inside and out.
Include Illustration
Keywords: House selling -- Interior decoration